Analyzing the Requirement of Students’ Advisory System on Campus - Tri Basuki, Kurniawan; Reynaldi, Brezensky (INTI International University, 2023)
This study addresses the issue of advisory systems among students enrolled in information systems study programs at Bina Darma University Palembang, Indonesia. These students have complied with an advisory system, but it is an offline advisory system, which causes some difficulties for the students and supervisors during the final report-making process. Previous research has highlighted the importance of an online advisory system that is more flexible, accessible, and convenient and can be developed using the latest technology. After several investigations, we propose a system with object-oriented analysis (OOA) and object-oriented design (OOD) techniques. We suggested a layout that makes use of Rich Internet Application (RIA) technology, offering responsive and interactive features that enable advisers and students to communicate in both directions at any time and from any location. Moreover, the RIA includes an online chat feature that makes it easier for supervisors and students to communicate even when they are not in the same room. The suggested design for the advising system that we presented in this paper is the outcome of our requirement analysis.